Computer Training of Rural Central American Teachers: Opportunities and Challenges - Michael R. McDermott; Theresa Pesl Murphrey; Gary Wingenbach (Journal of International Agricultural and Extension Education, 2013)
Quality education training in the Central American region is in great need of improvement to keep up with the educational rigor of other countries. While the use of information communication technology (ICT) can help improve training by giving students and teachers diverse learning opportunities, many rural and subsistence agricultural communities lack both resources and understanding of ICT. The purpose of this study was to describe Central American public school teachers’ perceptions of computers in education in their home countries. Sixty-two teachers served as respondents through their participation in the USAID program, Cooperative Association of States for Scholarships (CASS). The CASS program, located at Palo Alto Community College in San Antonio Texas, is a yearlong program consisting of teaching from CASS instructors and practicum with local dual language schools. The study instrument included three components: (a) computer knowledge growth, (b) home country worksite conditions, and (c) participants’ future plans. Respondents showed improved computer skills as a result of CASS training. Data revealed minimal to no ICT resources available in home country communities. Respondents shared their belief that the implementation of ICT is a critical need in their countries’ academic efforts. Upon completion of the program, these Central American teachers reported being equipped to function as change agents in their rural and subsistence agricultural communities. A longitudinal study focusing on teacher impact within their local communities is recommended.
Keywords: Computers; ICT; Education; Central American; Rural schools